Faktor-Faktor Penyebab Terjadinya Kecelakaan Kerja Saat Mengelas di Atas Kapal - Johanes OW Hitalessy; M. Furqon Rochyana; Achmad Hidayat; Isman Hidayat (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this study is to determine the causes of welding accidents on-board. The problem of work accidents is caused by the lack of the ship’s crew discipline to use the safety equipment while working. The data processing method was using descriptive method. The researchers tried to observe the cases that often occur on the ship related to the previous problem and note the causes and solutions to improve the ship’s crew discipline while working. The main potential hazards for hot work activities on vessels are fire and explosion. The implementation of the hot work permit system at Merak, Banten Port is in accordance with NFPA 51 B 2009 of Standard Fire Prevention during Welding, Cutting, and other Hot Work.